Pengamanan Data File Teks (Word) Menggunakan Algoritma RC4 - Dedy Ronald Saragi; Janter Manuel Gultom; Jose Andreas Tampubolon; Indra Gunawan (Universitas Budi Darma, 2020)
Data security on computers can provide a protection for our data. Cryptographic techniques are very important techniques in securing data. Cryptography is the science of encryption techniques where the